(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This study evaluated the effect of pretransplant desensitization therapy on ultrasound, laboratory, and histological parameters of kidney grafts in highly sensitized recipients. The study included 31 patients who underwent living-related kidney transplantation under conditions of high immunological sensitization. Of these, 18 (58.1%) were men and 13 (41.9%) were women, with a mean age of 43.7 ± 8.4 years. The mean pretransplant PRA level was 72.4 ± 8.7%; 18 patients (58.1%) had detectable DSA, and in 11 patients (35.5%) DSA levels exceeded 3000 MFI. All patients received a combined desensitization protocol including rituximab, 3–5 sessions of plasmapheresis, intravenous immunoglobulin, and baseline immunosuppression with mycophenolate mofetil and low-dose tacrolimus before transplantation. In 25 patients (80.6%), PRA decreased by at least 50% from baseline, and in 14 patients DSA levels fell below 1000 MFI, allowing transplantation to be performed after a negative final cross-match. In the source data, PRA and DSA showed a representative decline from 70% to 15% and from 3800 to 550 MFI, respectively. Early post-transplant follow-up showed that no cases of acute cellular or humoral rejection were recorded in this group under the applied treatment strategy. These findings indicate that desensitization therapy can substantially reduce the immunological burden before transplantation and create conditions for successful graft implantation and early postoperative stability in highly sensitized recipients.